2012
DOI: 10.1371/journal.pbio.1001433
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Early Adipose Commitment by Zfp521

Abstract: Zfp521 is a novel antiadipogenic transcription factor that helps to determine the identity of a mesenchymal cell as bone or fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 45 publications
6
123
0
2
Order By: Relevance
“…Overexpression of Zfp423 in NIH 3T3 fibroblasts was sufficient to confer adipogenic potential in vitro (Gupta et al, 2010). A close paralog to Zfp423 is Zfp521, an established negative regulator of preadipocyte commitment (Kang et al, 2012). Overexpression of Zfp521 in multipotent C3H10T1/2 cells inhibited adipogenesis, whereas knockdown of Zfp521 had the opposite effect (Kang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of Zfp423 in NIH 3T3 fibroblasts was sufficient to confer adipogenic potential in vitro (Gupta et al, 2010). A close paralog to Zfp423 is Zfp521, an established negative regulator of preadipocyte commitment (Kang et al, 2012). Overexpression of Zfp521 in multipotent C3H10T1/2 cells inhibited adipogenesis, whereas knockdown of Zfp521 had the opposite effect (Kang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A close paralog to Zfp423 is Zfp521, an established negative regulator of preadipocyte commitment (Kang et al, 2012). Overexpression of Zfp521 in multipotent C3H10T1/2 cells inhibited adipogenesis, whereas knockdown of Zfp521 had the opposite effect (Kang et al, 2012). Furthermore, Zfp521 knockout embryos exhibited enlarged BAT and increased white adipocyte numbers at E18.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene was found to present lower methylation levels in IR than in IS patients in association with increased transcription levels. Even though the functional association with the development of IR or T2D remains to be elucidated, future exploration of the role of this gene could reveal a novel mechanism involved in the development of IR and T2D in line with other zinc finger proteins, which are associated with adipogenesis, 37,38 T2D, or insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have a high adipogenic potential in vitro and in vivo and express the zinc finger protein 423 (ZFP423), a transcription factor involved in preadipocyte determination in vivo (Gupta et al, 2010;Gupta et al, 2012). Recently it has been shown that another transcription factor, zinc finger protein 521 (ZFP521), can regulate adipocyte development by inhibiting the expression of ZFP423 (Kang et al, 2012).…”
Section: Development Of Vertebrate Adipose Tissuementioning
confidence: 99%